Classical philosophy: influence the education philosophy of age - Mudafiatun Isriyah; Blasius Boli Lasan (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
Education with philosophy has a close relationship because philosophy is a viewof life that leads to the goal of education. According to Dewey, changes that occur in society must exist and inevitable because education is always changing. The perennialism view at the moment that education is regarded as a container to direct the center of culture. While human beings are able to solve the problem and achieve its goals rationally. This condition of development in the flow of philosophy one of which is essentialism. And education as a tool to process humanize human, with the difference of orientation and philosophy that became his belief. Differences philosophy in a nation will bring a difference in the perspective or purpose of education itself. Learning with the P4C contributes to raising children to be sensitive individuals who respect different perspectives and are able to shape their own rights, have ethical values, take care and improve themselves, and embrace new ideas.